Student Attendance System Using Fingerprint and Raspberry Pi with Notification - Muhammad Rasya; Atthariq Atthariq; Muhammad Nasir; Taufik Taufik (Jurnal Teknologi Rekayasa Informasi dan Komputer, 2025)
Fingerprint is an application designed to meet the needs of fast data using fingerprint verification. A fingerprint attendance machine is a type of biometric attendance machine that uses the student attendance/attendance method by detecting fingerprints. This fingerprint attendance is designed with a Fingerprint Sensor, LCD, and notification components. The purpose of this final project is to design an attendance device with fingerprints and a web database as a means of attendance. This system uses a Raspberry Pi as the controller. The study used fingerprints that had previously been verified in the database. In testing this attendance system, there are four tests, namely LCD testing, which is based on the results of the LCD only displaying all forms of data as a display that is by the registered database, fingerprint testing, and 10 times fingerprint testing of 20 people can produce a read. 97.7% of this value can be attributed to the average success rate of the fingerprint. web testing based on the results that have been tested on the Selenium IDE tool with successful output and no errors, the web is available 2 seconds after the fingerprint The data will be stored directly in the web database. Application testing, based on the results of application testing, namely, after fingerprint data enters the web database and immediately notifies the parents' Gmail account of the information from the application that the student has taken attendance, and the parents can see the attendance data or informationfrom the student.